Concept in formulating the ‘3w Theory’ in multidisciplinary research from the Qur’anic perspective - Islam, Md. Sirajul; Samsudin, Sofiah (International Journal of Scientific and Research Publication, 2015)
The ‘3w theory’ has been formulating in multidisciplinary research from the Qur’anic perspective. Consequently, based on our attention to the Holy Qur’an we found that the Qur’anic ayat (verses) refer to three question types – “what”, “why” and “what” which all are related to multidisciplinary research. Therefore, we name it ‘3w theory’ or ‘triple w theory’ = wwwT. The 1st (w) is for “what”, the 2nd (w) is for “why”, and the 3rd (w) is for “what” in research. The main aim of this paper is initially showing the perception about the 3w theory, its objectives as well as important in conducting research